Approaches for Modelling the Residual Service Life of Marine Concrete Structures. (12th January 2014) - Rahimi, Amir; Gehlen, Christoph; Reschke, Thorsten; Westendarp, Andreas
Abstract : This paper deals with the service life design of existing reinforced concrete structures in a marine environment. The general procedure of condition assessment for estimating the residual service life of structures before a repair measure is illustrated. For assessment of the residual service life of structures which have undergone a repair measure a simplified mathematical model of chloride diffusion in a 2-layer system is presented. Preliminary probabilistic calculations demonstrate the effect of various conditions on the residual service life. First studies of the chloride diffusion in a 2-layer system have been conducted using the finite element method. Results of a long-term exposure test are presented to illustrate the performance of two different repair materials. The distribution of residual chlorides after application of a repair material is being studied in laboratory investigations. The residual chlorides migrate from the concrete layer into the new layer immediately after the repair material has been applied to the concrete member. The content and gradient of residual chlorides, along with the thickness and the chloride ingress resistance of both the remaining and the new layer of cover, will determine the residual service life of the repaired structures.